Preparation and Characterization of Polypropylene/Carbon Nanotubes (PP/CNTs) Nanocomposites as Potential Strain Gauges for Structural Health Monitoring - Bartolomeo Coppola; Luciano Di Maio; Loredana Incarnato; Jean-Marc Tulliani (Nanomaterials, 2020)
Polypropylene/carbon nanotubes (PP/CNTs) nanocomposites with different CNTs concentrations (i.e., 1, 2, 3, 5 and 7 wt%) were prepared and tested as strain gauges for structures monitoring. Such sensors were embedded in cementitious mortar prisms and tested in 3-point bending mode recording impedance variation at increasing load. First, thermal (differential scanning calorimetry (DSC), thermo-gravimetric analysis (TGA)), mechanical (tensile tests) and morphological (FE-SEM) properties of nanocomposites blends were assessed. Then, strain-sensing tests were carried out on PP/CNTs strips embedded in cementitious mortars. PP/CNTs nanocomposites blends with CNTs content of 1, 2 and 3 wt% did not show significant results because these concentrations are below the electrical percolation threshold (EPT). On the contrary, PP/CNTs nanocomposites with 5 and 7 wt% of CNTs showed interesting sensing properties. In particular, the best result was highlighted for the PP/CNT nanocomposite with 5 wt% CNTs for which an average gauge factor (GF) of approx. 1400 was measured. Moreover, load-unload cycles reported a good recovery of the initial impedance. Finally, a comparison with some literature results, in terms of GF, was done demonstrating the benefits deriving from the use of PP/CNTs strips as strain-gauges instead of using conductive fillers in the bulk matrix.